Green-synthesized silver nanoparticles with aqueous extract of green algae Chaetomorpha ligustica and its anticancer potential - Al-Zahrani Sabah Ahmed (De Gruyter, 2021)
Marine green algae are rich in various bioactive components with known anticancer activity. Some anticancer drugs present in green algae are in clinical trials nowadays. Algae-mediated silver nanoparticles (AgNPs) have been of a great interest in cancer treatment due to their unique physico-chemical properties. In this study, we evaluate the anticancer efficiency of marine alga Chaetomorpha ligustica collected from the Arabian Gulf against colon cancer cell lines HT29 and HCT116. The anticancer potential of biosynthesized AgNPs from C. ligustica extract is also reported. Fourier transform infrared (FTIR) spectroscopy and gas chromatography-mass spectrometry analyses were used to identify the phytoconstituents present in algae extract. The synthesized AgNPs were confirmed via UV-Vis spectroscopy, whereas their morphology and stability were recorded by transmission electron microscopy (TEM), zeta potential, and zetasizer. We recorded absorption peak at 420 nm; TEM images showed an average size of 8.8 nm, whereas zeta potential and zetasizer study showed aggregation of nanoparticles. FTIR spectroscopy peaks of C. ligustica AgNPs were a little different from those of the C. ligustica extract. Both extracts showed cytotoxicity against cancer cell lines in a dose-dependent manner, but nanoparticles were found to be more toxic than algae extract. HT29 was found to be more sensitive than HCT116. For the first time, species of C. ligustica have been used and reported for the synthesis of nanoparticles. C. ligustica and its biogenic nanoparticles need to be scaled up for many biomedical applications especially in cancer research.